2002
DOI: 10.1002/dev.10071
|View full text |Cite
|
Sign up to set email alerts
|

Fetal activity following stimulation of the mother's abdomen, feet, and hands

Abstract: Fetal activity during midgestation (M age=19.8 weeks) was studied in response to vibratory stimulation of the mother's abdomen (at the height of the fetal head), foot massage, hand massage, or control condition (no stimulation). Consistent with previous research conducted during midgestation, the fetuses of mothers who received two trials of 3-sec, 60-Hz vibratory stimulation did not show changes in movement. In contrast, the fetuses of mothers who received a 3-min foot massage showed greater movement than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
(32 reference statements)
0
1
1
Order By: Relevance
“…Additionally, a significant decrease was found in STAI scores while a significant increase occurred in overall fetal movements after foot massage. In general, both studies demonstrated a reduction in maternal anxiety although the present study did not show the significant effect of foot reflexology on fetal movements (34).…”
Section: Discussioncontrasting
confidence: 79%
“…Additionally, a significant decrease was found in STAI scores while a significant increase occurred in overall fetal movements after foot massage. In general, both studies demonstrated a reduction in maternal anxiety although the present study did not show the significant effect of foot reflexology on fetal movements (34).…”
Section: Discussioncontrasting
confidence: 79%
“…Inter-rater reliability, calculated on one-third of the sample for two observers, yielded the following Kappa values: isolated fetal arm movements 9 = 0.87, isolated fetal leg movements = 0.86, fetal trunk movement = 1.0. Our method was, therefore, found to be valuable (32). Then, we calculated as the mean values for each of the 5 min periods (neutral, happy or sad, and next neutral).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why hand massage was used when the hand is so distal from the liver. However, other distal massages like foot massage have even affected fetuses [36].…”
Section: Pain Is Reduced By Massage Therapymentioning
confidence: 99%
“…But both types of massage involved the stimulation of pressure receptors, so it is not surprising that they both increased body temperature and they were equivalent on their positive effects on sleep and autonomic responses. The pain relief effects may have related to the increased serotonin (pain-relieving transmitter) levels that are typically noted after massage therapy [36]. In the other randomized controlled study "High force versus low force" massage (moderate versus low pressure massage) were compared for their effects on low back pain (N=56 females) [44].…”
Section: Pain Is Reduced By Massage Therapymentioning
confidence: 99%